2012
DOI: 10.1002/cne.23092
|View full text |Cite
|
Sign up to set email alerts
|

Visual inputs to the mushroom body calyces of the whirligig beetle Dineutus sublineatus: Modality switching in an insect

Chan Lin,
Nicholas J. Strausfeld

Abstract: The mushroom bodies are prominent lobed centers in the forebrain, or protocerebrum, of most insects. Previous studies on mushroom bodies have focused on higher olfactory processing, including olfactory‐based learning and memory. Anatomical studies provide strong support that in terrestrial insects with mushroom bodies, the primary input region, or calyces, are predominantly supplied by olfactory projection neurons from the antennal lobe glomeruli. In aquatic species that generally lack antennal lobes, the caly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Opsin duplications were predominantly found in species with behaviours often guided by visual cues, and in many of these species (see references), vision has been shown to be the primary cue for such behaviours: flower visitation ( Larinus minutus , Brassicogethes aeneus 51 and Heterochelus sp. 52,53 ), predation (coccinellids 54 , gyrinids 55,56 , Thanasimus formicarius , Carabus granulatus , Metrius contractus ), host plant detection (chrysomelids 57,58 , coccinellids 59 ), and mate recognition (buprestids 60 ). Duplications were notably absent in nocturnal species, with the exception of the nocturnal active predator, Carabus granulatus , which has been shown to possess a number of spectrally distinct photoreceptors 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Opsin duplications were predominantly found in species with behaviours often guided by visual cues, and in many of these species (see references), vision has been shown to be the primary cue for such behaviours: flower visitation ( Larinus minutus , Brassicogethes aeneus 51 and Heterochelus sp. 52,53 ), predation (coccinellids 54 , gyrinids 55,56 , Thanasimus formicarius , Carabus granulatus , Metrius contractus ), host plant detection (chrysomelids 57,58 , coccinellids 59 ), and mate recognition (buprestids 60 ). Duplications were notably absent in nocturnal species, with the exception of the nocturnal active predator, Carabus granulatus , which has been shown to possess a number of spectrally distinct photoreceptors 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Large MBs with developed calyces are therefore not limited to species which rely predominately on olfactory information to navigate in their environment. They can also be found in aquatic beetle species which navigate mainly by vision (Lin and Strausfeld, 2012). It remains to be investigated if the MBs play a role in visual learning in other insect orders as well.…”
Section: Discussionmentioning
confidence: 99%
“…The upper and lower eyes supply a separate lamina and medulla, relays from which supply a bilobed lobula. A previous description demonstrated that a unique attribute of the upper eye medulla is its relays supplying exclusively the visual calyces of the paired mushroom bodies [11]. Here we describe a further peculiarity of this optic lobe, which is the presence of a lobula plate exclusively serving the lower eye.…”
Section: Introductionmentioning
confidence: 55%
“…Posteriorly, the upper lobe of the lobula appears split into smaller volumes imposed by parallel bundles of axons (Figure  2C,D, arrows). These axons originate from the upper medulla and project inwards to the medial protocerebrum and then to the mushroom body calyces [11]. These observations suggest that in the adult whirligig beetle there are distinct functional differences between the upper aerial eyes and the lower aquatic eyes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation